Ditadura militar no Brasil: a consciência histórica de estudantes de uma escola pública - Silva, Joyci Viegas de Freitas (2022)
This study selected the theme of the Military Dictatorship in Brazil to investigate the process of development of historical consciousness, from the teaching of history in basic education schools. We are currently experiencing the intensification of the national debate on sensitive topics related to our memory. Historical awareness becomes, in this sense, an important reference for the teaching of history, within the theory of Didactics of History. From this perspective, the present text (the result of research developed within the scope of the Graduate Program in Teaching in Basic Education at UFG) analyzed the process of executing an extension project for the formation of history teachers (PIBID): the characters of the Military Dictatorship in a public school in Goiânia. Through various records made by students, whether drawings, transcribed or recorded testimonies, reports, political posters or small videos, it was found that much remains of this period in the youth daily life, highlighting the abuse of police violence in cities against youth and the problem of access to information. These records also made it possible to analyze the way in which the study of a historical theme from this unfinished past influences the formation of the historical orientation of these subjects in the present. The results were analyzed and an Educational Product was elaborated, called “Teaching about dictatorship with democracy”. Such Educational Product brings two proposals for teaching this content, seeking to give a different meaning to the school spaces from the student protagonism. Thus, it is expected that the history teacher, when teaching Military Dictatorship, allows students a formation permeated by democratic experiences and stimulus to autonomy in the construction of their own knowledge and acting in the present world.